KEANEKARAGAMAN PLANKTON DI DANAU RAJA KABUPATEN INDRAGIRI HULU SEBAGAI RANCANGAN KAMUS VISUAL PEMBELAJARAN BIOLOGI SMA - Suwarno, Nella; Fauziah, Yuslim; Nursal, Nursal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to be used as a source of information on the diversity of plankton species in danau raja. The study was conducted in Danau Raja, Indragiri Hulu Regency in April 2019. The parameters measured were biological parameters and physical chemical parameters of the waters. The research design is the stage of field data collection carried out with exploratory research, while the data collection is carried out using survey methods. This research was conducted in 4 stations with a purposive sampling technique. The method in this study consists of 2 stages, In the study of visual dictionary design using the Four-D model which consists of four stages, namely defining, designing, developing, and dissemination. The data obtained were analyzed descriptively.The results of this study showed that the composition of fitoplankton in danau raja was found in 5 classes, 20 species and 188 individuals. The most zooplankton compositions are Bosmina meridionalis and Diaphanosoma brachyuran with a proportion of 50%. The highest abundance of phytoplankton was found at station IV and the lowest was at station I. The highest phytoplankton diversity index was found at station IV and the lowest was at station I. The highest abundance of zooplankton was obtained at station III and station IV, while at station I and station II there were no zooplankton. The highest zooplankton diversity index was found at station III and station IV while at station I and station II no zooplankton was found.Key Words: Fitoplankton, Zooplankton, Purposive Sampling